Antimicrobial Susceptibility Profile of Multi Drug Resistant Acinetobacter and Pseudomonas against Polymyxin E and Tigecycline - Zuhair Ali Rizvi , Zuhair Ali Rizvi; Rabbia Khurs, Rabbia Khurs; Maira Zafar , Maira Zafar; Saira Anwar, Saira Anwar; Ali Hassan Malik, Ali Hassan Malik (Students’ Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Antimicrobial Resistance of Multidrug Resistant (MDR) Acinetobacter and Pseudomonas against Polymyxin E and Tigecycline is increasing exponentially. However, a wide range of susceptibility profiles to these drugs have been noted in different parts of the world. Objective: To determine the antimicrobial susceptibility of MDR Acinetobacter and Pseudomonas against Polymyxin E and Tigecycline. Materials & Methods: This cross-sectional study was conducted in Medical Intensive Care Units (MICU) of Holy Family Hospital for a duration of 1 year after ethical approval from Institutional Research Forum (IRF) of Rawalpindi Medical University. Hospital records of patients admitted in MICU were included using consecutive sampling technique. Organisms that were not MDR Acinetobacter or MDR Pseudomonas were excluded. Antimicrobial resistance of included isolates was noted against Polymyxin E & Tigecycline. Variables like gender, age, organism, site of isolation and antimicrobial resistance against Polymyxin E & Tigecycline were noted. Data was entered and analyzed using SPSS v20. Results: Mean age of isolation of MDR Acinetobacter was 35.79±15.55 years while mean age of isolation of MDR Pseudomonas was 26.54±7.83 years. The difference was very highly statistically significant. MDR Acinetobacter & MDR Pseudomonas both were more commonly isolated from male as compared to female patients. MDR Acinetobacter & MDR Pseudomonas were most commonly isolated from catheter tips, followed by blood. However, MDR Pseudomonas was not isolated from urine. Antimicrobial resistance against Polymyxin E & Tigecycline was surprisingly high. Conclusion: The antimicrobial resistance of MDR Acinetobacter or MDR Pseudomonas was alarmingly high. Therefore, proper strategies should be formulated regarding use of antimicrobial agents.